Fatty Acids, Amphiregulin Production, and Lung Function in a Cohort of Midwestern Veterans - Hanson, Corrine; Ponce, Jana; Isaak, Mia; Heires, Art; Nordgren, Tara; Wichman, Chris; Furtado, Jeremy D.; LeVan, Tricia; Romberger, Debra (Frontiers in Rehabilitation Sciences, 2022)
Rationale: The relationship between many fatty acids and respiratory outcomes remains unclear, especially with regard to mechanistic actions. Dysregulation of lung repair processes is a key feature of chronic lung disease and may impact the potential for pulmonary rehabilitation, but the mechanisms underlying dysfunctional repair following lung inflammation are unclear. The epidermal growth factor receptor agonist amphiregulin (AREG) has been demonstrated to promote lung repair following occupational dust exposure in animals. Studies suggest the polyunsaturated fatty acid (PUFA) docosahexaenoic acid (DHA) may enhance the production of AREG. The objective of this study was to determine the relationship between fatty acids and lung function in a population of veterans and determine if fatty acid status impacts concentrations of AREG. Materials and Methods: Data were collected from a cross-sectional study of veterans within the Nebraska-Western Iowa Health Care System who had greater than 2 years experience working on a farm. Whole blood assays were performed to quantify AREG concentrations via a commercially available ELISA kit. Fatty acids from plasma samples from the same patients were measured using gas-liquid chromatography and intakes were quantified with a validated food frequency questionnaire. Linear regression models were used to determine whether plasma fatty acid concentrations or intakes of fatty acids predicted lung function or AREG concentrations. A p-value less than 0.05 was considered statistically significant. Results: 90 participants were included in this analysis. In fully adjusted models, plasma concentrations of fatty acids were associated with AREG production, including the PUFA eicosapentaenoic acid (EPA) (β=0.33, p=0.03) and the monounsaturated fatty acid octadecenoic acid: (β=-0.56, p=0.02) The omega-3 PUFA docosapentaenoic acid (DPA) was positively associated with lung function (β=0.28, p=0.01; β=26.5, p=0.05 for FEV1/FVC ratio and FEV1 % predicted, respectively), as were the omega-6 PUFAs eicosadienoic acid (β=1.13, p<0.001; β=91.2, p=0.005 for FEV1/FVC ratio and FEV1 % predicted, respectively) and docosadienoic acid (β=0.29, p=0.01 for FEV1/FVC ratio). Serum concentrations of both monounsaturated and saturated fatty acids were inversely associated with lung function. Conclusion: Opposing anti- and pro-inflammatory properties of different fatty acids may impact the lung function in this population, in part by regulating AREG induction.